2016
DOI: 10.7863/ultra.15.09074
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Prenatal Sonographic Findings of Duodenal Obstruction and Adverse Outcomes

Abstract: Prenatal sonographic findings of duodenal obstruction were not associated with adverse outcomes; however, they may be helpful for differentiating the cause of duodenal obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
3
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 35 publications
1
12
3
4
Order By: Relevance
“…Uzamış duodenal ileusu önlemek için, mega duodenum (duodenum çapı 5 cm'den büyük olan) olgularında plikasyon ve tapering gerekebilir (16). Çalışmaların sadece 5'inde operasyonlara yer verildiği görüldü (6,7,9,13,15). Bunun sebebi çalışmaların önemli bir kısmının klinik süreçten ziyade hastalığın belirli bir kesitini incelemeyi amaçlamasından kaynaklanmaktadır.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Uzamış duodenal ileusu önlemek için, mega duodenum (duodenum çapı 5 cm'den büyük olan) olgularında plikasyon ve tapering gerekebilir (16). Çalışmaların sadece 5'inde operasyonlara yer verildiği görüldü (6,7,9,13,15). Bunun sebebi çalışmaların önemli bir kısmının klinik süreçten ziyade hastalığın belirli bir kesitini incelemeyi amaçlamasından kaynaklanmaktadır.…”
Section: Discussionunclassified
“…Operasyonlarda dokuz olguda (% 66.5) tip1 atrezi, beş olguda (%31) annüler pankreas, iki olguda (%12.5) tip 2 atrezi görüldü. Hastalarda ortalama TPN alma süresi 8.4 (6)(7)(8)(9)(10)(11)(12)(13)(14) gün, oral beslenmeye başlama süresi 6.31(5-9) gün ve ortalama yatış süreleri 17.56 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) gündü. Olguların hiçbirinde cerrahi komplikasyon görülmedi ve tüm olgular tam iyileşme ile taburcu edildi.…”
Section: Bulgularunclassified
“…The presence of polyhydramnios was defined as an amniotic fluid index greater than 25 cm or a maximum vertical pocket exceeding 8 cm during pregnancy. At the level of the 'double bubble' sign, the maximum transverse diameter of the dilated duodenum (inner wall to inner wall) was measured to record the maximum dilatation of the duodenum [6]. (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…CDO patients need to be operated on in the neonatal period after birth. The long-term survival rate has reached 86-90% with the development of CDO surgical operations in recent years [5,6]. Previous studies have shown that early diagnosis and surgery can reduce the incidence of metabolic disorders, duodenal obstruction and intestinal failure [1,7].…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] In CDO, the dilated stomach and first part of the duodenum appeared side by side across the midline of the upper fetal abdomen during prenatal sonography, which is known as the "double-bubble" sign. 7 This distinguishing feature has brought about great advances in the diagnosis since the later 1970s. 8 Delayed return of normal duodenal function necessitating a prolonged hospital stays may often follow the operative treatment of neonatal duodenal obstruction.…”
Section: Introductionmentioning
confidence: 99%